Kinetics-Controlled Simple Method for the Preparation of Au@Ag Hierarchical Superstructures for SERS Analysis - Mengqi Lyu; Ming Jiang; Hanting Yu; Kailiang Wu; Peitao Zhu; Yingke Zhu; Yan Xia; Juan Li (Inorganics)
Silver nanostructures exhibit exceptional surface-enhanced Raman scattering (SERS) performance due to their strong plasmonic resonance. However, their practical applications are often hindered by structural instability, leading to deformation and performance degradation. In this study, we developed a kinetics-controlled synthetic strategy to fabricate gold-encapsulated silver (Au@Ag) hierarchical superstructures (HSs) with enhanced SERS activity and stability. By leveraging polyvinylpyrrolidone (PVP) as a surface modifier and precisely regulating the introduction rate of reaction precursors, we achieved meticulous control over the galvanic replacement kinetics, thereby preserving the structural integrity of pre-synthesized Ag HSs during the formation of Au@Ag HSs. The resulting well-defined Au@Ag HSs demonstrated superior SERS performance, achieving a detection limit of 10−9 M for crystal violet (CV) while exhibiting outstanding signal reproducibility (relative standard deviation, RSD = 11.60%). This work provides a robust and scalable approach to designing stable, high-efficiency SERS-active nanostructures with broad potential in analytical and sensing applications.